2012
DOI: 10.1159/000337027
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recurrence Rate of Large and Difficult to Treat Cutaneous Squamous Cell Carcinomas after Superficial Radiotherapy

Abstract: Background: Surgical excision is the gold standard for cutaneous squamous cell carcinoma (cSCC), however its application is limited in specific cases. Superficial radiotherapy (RTx) is an alternative treatment option, but long-term follow-up data are limited. Objective: To determine the outcome of superficial RTx of cSCC in correlation to histological differentiation grade and tumor localization. Methods: The outcome of 180 large cSCCs after superficial RTx between 1960 and 2004 was retrospectively reviewed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 68 publications
5
32
0
2
Order By: Relevance
“…547,581,584 In one study, location in the ear and scalp region was found to be significantly associated with relapse of tumour compared with other sites (p = 0.025). 591 Age and tumour size were also significantly correlated with risk of relapse in this study (p = 0.012 and p < 0.0001, respectively), with a trend towards better outcome with well-differentiated tumours, although statistical significance was not reached (p = 0.1). Two studies (with 155 patients in total) assessed only nasal SCCs, with a pooled average local recurrence of 5.6% (95% CI 2.6% to 9.7%).…”
Section: External Radiotherapymentioning
confidence: 43%
See 4 more Smart Citations
“…547,581,584 In one study, location in the ear and scalp region was found to be significantly associated with relapse of tumour compared with other sites (p = 0.025). 591 Age and tumour size were also significantly correlated with risk of relapse in this study (p = 0.012 and p < 0.0001, respectively), with a trend towards better outcome with well-differentiated tumours, although statistical significance was not reached (p = 0.1). Two studies (with 155 patients in total) assessed only nasal SCCs, with a pooled average local recurrence of 5.6% (95% CI 2.6% to 9.7%).…”
Section: External Radiotherapymentioning
confidence: 43%
“…Regional lymph node failure was also reported in three studies (comprising 272 patients in total), 547,585,591 giving an average regional recurrence of 2.6% on pooled analysis (95% CI 0.04% to 8.9%; I 2 = 70%) ( Figure 41). In both larger studies, 585,591 which included patients with SCCs of the nose and at various sites, respectively, the mean duration of follow-up was between 2 and 5 years.…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 66%
See 3 more Smart Citations